The jungle book - Kipling, Rudyard 1865-1936 (Oxford children's classics., 2007)
A children's classic, featuring Mowgli, the Indian boy brought up by wolves in the jungle, his companions, Baloo and Bagheera, and his enemy, Shere Khan.